ANALISIS SOAL-SOAL PADA BUKU TEKS MATEMATIKA KURIKULUM 2013 EDISI REVISI TAHUN 2014 KELAS XI BERDASARKAN KEMAMPUAN PENALARAN MATEMATIKA - Dyan Falasifa Tsani (Universitas Pekalongan, 2018)
The process of reasoning has a very strong connection with mathematic world, especially on problem solving skills. But in real life, teachers usually use textbook to measure how much do their students understand materials taught by the teachers. Hence, it is necessary to understand completely do the widely used mathematic textbook has led students to increase their mathematic reasoning skills. The method used were descriptive qualitative, with Competency Test’s problems in 2013 Curriculum text book revised in 2014 for 1 th grade used for research subjects. Documentation method was used as data collection method. Problems analysis guide was based on mathematic reasoning skills indicator according to NCTM. The analysis result tells that from 225 problems analyzed there were 76 problems fulfilled the indicator 1, 110 problems fulfilled the indicator 2, 30 problems fulfilled the indicator 3 and 183 problems fulfilled the indicator 4. Analysis also shows that based on mathematic reasoning skills, from 225 problems there were only 8 problems haven’t fulfilled the mathematic reasoning skills with 3,56% presentation number. While the rest there were 217 problems have fulfilled the mathematic reasoning skills with 96,45% presentation number with 49 problems with 21,78% presentation number have a good criteria, 80 problems with 35,56% have an average criteria and 88 problems or 39,11% have a low criteria.